The Value Of Ethics And Futures Thinking On Firms Strategic Decision Making - Chalesty Onie, Jumi; Helen Tan, Siew Hong (2023)
This paper explores the strategic convergence of ethical principles and foresight practices, and its impact on firm's strategic decision making within the context of healthcare. Healthcare is an essential part of society, and effective strategic decision-making is crucial for healthcare organizations to ensure efficient and high-quality delivery of care. Ethical considerations are especially important as the actions and decisions made by healthcare professionals impact the lives of individuals. Futures thinking, also known as strategic foresight, is a process of thinking critically about possible future scenarios, identifying opportunities and threats, and developing strategies to address them. Despite the potential benefits of incorporating ethical and foresight practices into strategic decision-making, research suggests that healthcare organizations may not be fully utilizing these practices in the private healthcare sector. In addition, there is a dearth of in-depth discussion which explores the relationships between ethics, futures thinking, strategic decision-making, and healthcare organizations' performance. Therefore, a conceptual framework linking ethical futures thinking and strategic decision making is proposed, to explore: (1) the concept of ethical future thinking and its role in strategic decision making; (2) the key success factors for nurturing ethical future thinking in private healthcare organizations; and (3) the challenges that might impede the effort. The proposed framework highlights the potential value of incorporating ethical and futures thinking practices into healthcare decision-making processes, and that it will further support the attainment of the UN's Sustainable Development Goal 3 (SDG3), namely good health and well-being.